Metode Penyelesaian Sengketa Batas Desa UPT Tambak Sari Kecamatan Poto Tano Kabupaten Sumbawa Barat - Rasyid Ridha; Agus Kurniawan; Febrita Susanti; Sri Apriani Puji Lestari (Jurnal Planoearth, 2019)
UPT Tambak Sari is one of the expansion villages in the sub- district of Poto Tano, which  has  problems  against  village  boundary  disputes  with  surrounding  villages,  thus  inhibiting the process of setting the village boundary to be definitive, therefore it is necessary to Settlement of the village boundary UPT Tambak Sari. The purpose of this research is to know  the  process  of  implementing  and  resolving  boundary  disputes  for  UPT  Tambak  Sari village.   The   method   used   is   a   qualitative   description   through   participatory   mapping approach es  as well  as  referring  to the  Indonesian  Ministry of  Home  Affairs  Regulation  No.  45 2016 of village boundaries determination and affirmation guidelines. The results obtained  from this research is the implementation of the boundary of village boundaries conducted in the  internal  Cartometris  village,  and  then  carried  out  the  boundary  settlement  deliberation  between  villages  with  the  exposure of  Toponimi  and  village  boundary  segments,  but weak Regulations and information sources relating to indicative village boundaries precipitate the boundary disputes between villages. In the village boundary determination process has also been  agreed  on  the  mechanisms  of  dispute  the  village  boundary,  the  mechanism  that agreed is the report of the village boundary dispute to the dispute resolution team was then  carried out mediation and Deliberation, if there is no agreement then will be in the process of  adjudication, in this process of dispute settlement of the village boundary UPT add Sari can be  resolved  at  the  mediation level  based  on  the  joint  decision  of  the  District  regent  of  Sumbawa The history of village formation and regulation.